Risk factors for ectopic pregnancy: an institutional study in a tertiary care hospital - Ghadei, Ranjita; Mohanty, Swayamsiddha; Mishra, Sushree Sovana; Giri, Debashis (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ectopic pregnancy is the leading cause of maternal death during the 1st trimester of pregnancy, accounting for approximately 10% of all pregnancy related deaths. A better understanding of ectopic pregnancy risk can help prevent its occurrence. The present study was designed to evaluate the ectopic pregnancy risk factors and their strength of association with ectopic pregnancy at a tertiary care hospital. Methods: It was a prospective study with 104 cases of ectopic pregnancy and 125 controls conducted in the Department of Obstetrics and Gynecology, SCB Medical College, Cuttack for a period of 1 year. Detailed history suggestive of risks factor for ectopic pregnancy, menstrual and obstetrics history was taken. General, systemic, abdominal and vaginal examination was done. Diagnosis of ectopic pregnancy was confirmed by clinical examination, urine pregnancy test, ultrasonography and culdocentesis and only confirmed cases were included in the study group. Healthy pregnant women were taken as control group. Results: The study revealed that the risk of ectopic pregnancy was associated with the traditional risk factors including previous EP [Adjusted odds ratio (AOR) = 9.98, 95% CI: 0.89-11.1%], previous infertility (AOR= 7.29, 95% CI:2.53-21.0) and previous history of sterilization (AOR=12.47,95% CI: 3.50 - 44.4) and previous history of abortion (AOR= 3.10, 95% CI: 1.53-6.30). Age comparison between cases and controls revealed that the ODDS of having ectopic pregnancy was 4 times in the age group 30 to 35 years as compared to uterine pregnancy and this difference was statistically significant (P value = 0.007). Conclusions: Risk factors such as previous ectopic pregnancy, induction of ovulation, intra uterine device usage, abortion as well as increased maternal age along with recent diagnostic tools aid in early detection of ectopic pregnancy in women resulting in proper and timely treatment.